Vegetative Propagation of Eureka Seedless Lemon (Citrus limon L.Cv Eureka seedless) using Different Types of Stem Cutting and Concentrations of Indole-3-Butyric Acid in Winter - Gnawali, Pushpa; Gurung, Maya; Kadel, Sudip; Bhantana, Samriddha; Chand, Narendra Bahadur; Pathak, Rukmagat; Poudel, Puspa Raj (Nepalese Horticulture, 2022)
Citrus can be propagated successfully through stem cutting. However, success of the propagation is depends on various internal as well as external factors. The 2*7 factorial Randomized Complete Block Design (RCBD) experiment was conducted at the Institute of Agriculture and Animal Sciences, Paklihawa Campus, Rupandehi, Nepal from 22 November 2019 to 5 March 2020 to assess the interaction effect of types of stem cuttings and indole 3 butyric acid (IBA) concentrations on the vegetative propagation of Eureka seedless lemon in winter. Stem cutting types had two levels: hardwood and semi-hardwood cutting and IBA concentrations had seven different level i.e control, 500 ppm, 1000 ppm, 2000 ppm, 3000 ppm, 4000 ppm, and 5000 ppm respectively forming overall 14 treatments and three replications. Statistically, significant interaction effects were seen in root parameters. The highest total number of the root(18.00) were found in hardwood cuttings treated with 4000 ppm and lowest total number of roots(1.66) was found in semi-hardwood cuttings treated with 0 ppm of IBA. A statistically significant interaction effect was not found in most of the shoot parameters. However, maximum sprouting (93.33%), the average number of shoots (4.67), average length of the shoot (7.86), and minimum days for first sprouting (30.67 days) were found in hard wood cuttings treated with 4000 ppm IBA. Considering different root and shoot parameters, hardwood cuttings treated with 4000 ppm performed best for root and shoot development. Thus, hardwood cuttings treated with 4000 ppm IBA can be appropriate method for easy and early propagation of eureka seedless lemon.